2004
DOI: 10.1262/jrd.50.119
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Expression of Gastrin-releasing Peptide (GRP) in the Bovine Cervix

Abstract: Abstract. Gastrin-releasing peptide (GRP) has been suggested as a novel regulatory peptide in the female reproductive tract but the presence of GRP and GRP mRNA in the non-neurogenic tissue of the cervix has not yet been clarified. In the present study, immunohistochemistry and in situ hybridization were used to reveal the distribution of GRP immunoreactivity and expression of GRP mRNA in the bovine cervix. The cervixes from 21 non-pregnant and 20 pregnant cows, and 6 fetuses were used in the study. In the fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…[1, 2, 6, 7, 9, 24, 26]. Indeed this protein was by far the major stored and secreted form of proGRP processing in the pregnant sheep [26].…”
Section: Introductionmentioning
confidence: 99%
“…[1, 2, 6, 7, 9, 24, 26]. Indeed this protein was by far the major stored and secreted form of proGRP processing in the pregnant sheep [26].…”
Section: Introductionmentioning
confidence: 99%
“…It was found primarily in uterine gland epithelium at 20 and 140 days of gestation. Furthermore, GRP immunoreactivity has been described in the bovine uterus and cervix (Budipitojo et al., 2001, 2003, 2004a,b) as well as the placenta (Budipitojo et al., 2001). These investigators have suggested that GRP might play an important role in the autocrine and/or paracrine regulation of the intrauterine environment of both non‐pregnant and pregnant animals (Budipitojo et al., 2001, 2004a).…”
Section: Introductionmentioning
confidence: 99%